Efficacy evaluation of the state care plan for refugees in RN - Silva, Diana Ambrosio de Lima; Oliveira, Eliza Daiana Lopes de; Lima, Leonardo Jacob de; Silveira, Raquel Maria da Costa (Revista Aval, 2025)
article presents an evaluation of the effectiveness of the State Plan for Attention to Stateless Refugees and Migrants of Rio Grande do Norte, regarding axis 6, which provides guidelines for the inclusion of this population in the state's economic dynamics. Methodologically, participatory and results evaluation was carried out, with qualitative and quantitative data analysis, using five collection instruments: an exploratory interview, three semi-structured interviews and a focus group. The assessment was based on 4 dimensions of analysis: Guaranteed Citizenship, Perceived Citizenship, Lived Citizenship and Active Citizenship. As a result, it was possible to verify that, despite being recent, the migration policy in the state of RN, with regard to the evaluated axis, has been partially effective in the strategies for welcoming, developing and including these people in the territory through work, this is because other guidelines still require emergency policies to guarantee access to basic rights for this population.